Interactions Between Socioeconomic Status and Mental Health Outcomes in the Nigerian Context Amid COVID-19 Pandemic: A Comparative Study - Agberotimi, Samson F.; Akinsola, Olusola S.; Oguntayo, Rotimi; Olaseni, Abayomi O. (Frontiers in Psychology, 2020)
This study examines the mental health outcomes among the healthcare personnel and the general population and the role of socioeconomic status. Eight hundred and eighty-four (884) residents in Nigeria comprising 382 Healthcare Personnel and 502 general residents aged between 18 to 78 years (M = 28.75, SD = 8.17) responded to an online survey with measures of Impact of Event Scale-Revised (IES-R), Generalized Anxiety Disorder (GAD-7), Patient Health Questionnaire (PHQ–9) and Insomnia Severity Index. Collected data were subjected to statistical analysis using the SPSS v.25. Results revealed significant difference in the prevalence of depressive symptoms (χ2 = 14.26; df = 4; p <0.01); insomnia symptoms (χ2 = 40.21; df = 3; p< 0.01); posttraumatic stress symptoms (χ2 = 08.34; df = 3; p< 0.05) and clinical anxiety symptoms (χ2 = 06.71; df = 1; p <0.05) among healthcare personnel and the general population, with a higher prevalence reported by the healthcare personnel. Further, socioeconomic status significantly influences prevalence of depressive symptoms (χ2 = 04.5; df = 4; p <0.05). The study concluded that the prevalence of poor mental health outcomes during the COVID-19 crisis among Nigerians is worrisome. Also, the socioeconomic status of the citizens has serious implications on depressive symptoms. The study recommends that the government and stakeholders should pay attention to policy that will favor tele-mental health services and adequate palliative measures to cushion the psycho-economic impacts of COVID-19 on residents. Also, healthcare workers should be considered for better remuneration and other welfare benefits to sustain their wellbeing during the present and future pandemic.